PENGARUH KONDISI RUANGAN PENYIMPANAN OBAT TERHADAP KUALITAS KAPLET ASAM MEFENAMAT di PUSKESMAS KECAMATAN PONTIANAK KOTA - ., Ade Ria Ayu Fardhiani (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2013)
Mefenamic acid is a derivative of anthranilic acid is widely used by the public asan analgesic, antipyretic, and anti-inflammatory. Mefenamic acid is a drug which issensitive to light, temperature and humidity. This research aims to determine the qualityof mefenamic acid caplets that stored in Pontianak City community health centre as amatter of consideration in storage of both drugs in community health centre. Research hasbeen conducting by doing some observation on drug storage conditions such astemperature and humidity with non-experimental methods. Mefenamic acid samples weretaken twice during the research, mefenamic acid samples at the beginning and at the endof storage that had been stored for a month in storage room of each community healthcentre. The quality of mefenamic acid caplets evaluated, namely physical and chemicaltests. The results showed that the storage conditions at 4 community health centres do notall qualify, only Alianyang community health centre that qualified. Community healthcentres room temperature ranged from 25 to 33,3 C, humidity 52 to 88,3%. Temperatureand humidity affect the physical and chemical quality of mefenamic acid caplets in allexamination parameters except weight uniformity. Quality phsysical and chemical ofmefenamic acid caplet getting dropped after being stored for a month, but still meet therequirements of a good quality caplets.Keywords: mefenamic acid, temperature, humidity, health centre